Departamento de norte de Santander: efectos económicos y sociales derivados de la crisis nacional de Venezuela (2018)
The difficult situation that unfolded in Venezuela has generated great imbalances not only economic but social, in addition to diplomatic tension and deterioration in relations with other countries of the world as is the case of Colombia, a bilateral relationship that began mainly in the years 70 and that it became commercially dynamic with the mandate of Hugo Chávez since 1999; This diplomatic tension between the political leaders of Colombia and Venezuela generated a binational crisis linked to confrontations and accusations among their leaders, border closures and the deportation of thousands of Colombians living in Venezuela, thus causing negative effects to businessmen of both countries and a large percentage of the population on the border which is directly or indirectly involved with border trade.